2018
DOI: 10.1038/s41368-017-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

RANKL deletion in periodontal ligament and bone lining cells blocks orthodontic tooth movement

Abstract: The bone remodeling process in response to orthodontic forces requires the activity of osteoclasts to allow teeth to move in the direction of the force applied. Receptor activator of nuclear factor-κB ligand (RANKL) is essential for this process although its cellular source in response to orthodontic forces has not been determined. Orthodontic tooth movement is considered to be an aseptic inflammatory process that is stimulated by leukocytes including T and B lymphocytes which are presumed to stimulate bone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Given its control also of fibroblast differentiation, it is possible that asporin controls the interaction between PDL fibroblasts, osteoblasts and osteoclasts in the formation of Sharpey's fibers. These observations are also supported by previous studies showing that induction of the RANKL/OPG system in PDL fibroblasts leads to osteaoclast genesis and bone resorption in the event of tooth movement and compressive forces in the PDL (Yang et al, 2018). This is a mechano-sensitive process (Jacobs et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Given its control also of fibroblast differentiation, it is possible that asporin controls the interaction between PDL fibroblasts, osteoblasts and osteoclasts in the formation of Sharpey's fibers. These observations are also supported by previous studies showing that induction of the RANKL/OPG system in PDL fibroblasts leads to osteaoclast genesis and bone resorption in the event of tooth movement and compressive forces in the PDL (Yang et al, 2018). This is a mechano-sensitive process (Jacobs et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…65 RANKL is a member of the membrane-associated TNF ligand superfamily and is detected on osteoblasts, bone marrow stromal cells, activated T cells, periodontal ligament fibroblasts, cementoblasts and endothelial cells. [66][67][68][69] RANKL binds its receptor, receptor activator of NF-κB (RANK), expressed on the osteoclast precursor cells, resulting in the activation of the osteoclast. 70 The binding of RANKL to RANK finally activates the transcription of NFATc1, c-Fos and NF-κBrelated genes, which are upregulated in periodontitis 71,72 and modulate the proliferation, differentiation and activation of osteoclasts.…”
Section: The Role Of Il-1β In Periodontitismentioning
confidence: 99%
“…Shiotani et al (Shiotani, Shibasaki, & Sasaki, 2001) have shown the presence of RANKL in periodontal tissues during experimental tooth movement. RANKL produced by periodontal ligament and bone lining cells provide the major driving force for tooth movement and osteoclastogenesis in response to orthodontic forces (Yang et al, 2018). Local RANKL injection can recruit peripheral monocytes and macrophages (Jin, Li, & Yu, 2011) and has the ability to produce inflammatory cytokines such as interleukin (IL)-1b, IL-6, IL-11 and tumour necrosis factor-alpha (TNFα), which probably mediate bone remodelling by stimulating RANKL expression during orthodontic tooth movement (Kohli & Kohli, 2011;Saito, Saito, Ngan, Shanfeld, & Davidovitch, 1991).…”
Section: Discussionmentioning
confidence: 99%